Characterization of different stocks of macrobrachium rosenbergii and development of genetically improved strain through selective breeding - Shyla G (Department of Aquaculture, College of Fisheries, 2010)
Giant freshwater prawn Macrobrachium rosenbergii (de Man, 1879) is an important species suitable for culture in inland and low saline coastal water bodies. Information on the genetic structure and variation among cultured species are essential for genetic approaches to optimize conservation strategies and breeding programmes for improving stocks. DNA based markers can be used to assess more precisely the genetic variations in the entire genome. Natural populations of M. rosenbergii inhabiting the rivers in different geographical areas of India show wide variation in morphological traits and economic characters. The present work envisages studying the genetic diversity of wild populations of M. rosenbergii collected from different parts of India through phenotypic characters and molecular marker studies. It also aims to develop a superior strain by combining the desirable characters through selective breeding. In this study genetic characterization of Andhra Pradesh (AP), Orissa (OR) and Kerala (KR) stocks of Macrobrachium rosenbergii were done with RAPD and Microstellite markers. Marker analysis showed variation between stocks and AP showed more genetic distance from OR and KR populations.Moreover KR stock from Achankoil River showed slight similarity with AP. Phenotypic trait analysis was done with three stocks. Egg diameter, larval hatch fecundity, larval rearing period, survival rate and larval length were estimated. Highest egg diameter and hatch fecundity were shown by OR and KR populations. AP showed minimum larval rearing period and maximum survival rate. Maximum larval length was for KR. Stress tolerance studies were conducted in V and X stage of M.rosenbergii larvae with temperature, salinity, formaldehyde and ammonia to estimate the relative differences in the ability of different populations to withstand stressed conditions. Among base population KR population showed highest tolerance towards temperature, salinity, formaldehyde and ammonia.Stage wise tolerance variations also found in all populations. X stage showed more tolerance to all stressors except ammonia. Comparison of other economically important parameters such as disease resistance, quality of flesh, percentage survival, growth rate, percentage morphotypes and head tail ratio were also done. Disease resistance was tested with white tail virus and bacteria (Enterococcus aerogenes) by challenge study. In both studies KR population exhibited better tolerance than other populations. Prophenoloxidase activity and total haemocyte count was also estimated in infected prawns to check the immune response. Here again KR showed higher activity and count. Flesh quality of three populations was estimated by carcass proximate analysis. In this study, no variation in body composition was shown by three stocks. Percentage survival rate and weight gain of three populations in cage were estimated. Maximum survival rate was found in AP and highest growth was found in KR stock. Analysis of percentage morphotypes of various populations showed the maximum OC for AP and SM for OR stock, with no significant variations in percentage BC and female prawns, head tail ratio, which was calculated to find out the yield of meat revealed the least ratio for KR. Large healthy prawns of the three stocks were selected from families showing better performance. Breeding experiment was conducted to produce six crosses viz. Andhra Pradesh (male)×Orissa (female) APOR, Orissa (male) × Andhra Pradesh (female) ORAP, Andhra Pradesh (male) × Kerala (female) APKR, Kerala (male) × Andhra Pradesh (female) KRAP, Orissa (male) × Kerala (female) ORKR, Kerala (male) × Orissa (female) KROR. Different phenotypic characters and economically important traits of F1 generations of hybrids were also studied. KROR showed better egg diameter, hatch fecundity, larval survival rate and larval length. But larval rearing period was minimum for APKR. KROR showed resistance to viral and bacterial diseases, which was similar to that of KR and better than other hybrids. In cage culture APOR showed better survival rate, while growth rate was significantly higher for KROR, which was more than that of base populations. Analysis of percentage morphotypes showed a similar pattern as that of base populations. Lower head -tail weight ratio was shown by KROR, which was lower than that of KR. Estimation and comparison of heritability of weight of three better performing hybrids were done. From the data it was found that maximum heritability of weight was for KROR (.75) followed by APKR (.161) and APKR exhibited no heritability.